Intelectual capital Islamic work ethics and the performance of Bumiputera small and medium enterprises (SMES) experts views / Sakinah Mat Zin ...[et al.] - Mat Zin, Sakinah; Adnan, Ahmad Azrin; Nik Md Salleh, Nik Sarina; Che Mat, Rosfatihah; Abd Manaf, Khamisah; Setapa, Mariam (Universiti Teknologi MARA Kelantan, 2019)
Despite numerous efforts initiated by Malaysian government, Bumiputera entrepreneurs are still considered as incapable to compete with other groups in realizing business success. This study seeks to examine the intellectual capital (IC) and Islamic work ethics (IWE) that contribute to higher performance of SMEs among Bumiputera in Malaysia. In doing so, the measurement instruments are developed based on previous literature reviews and refined by expert validation. Informal interviews were held individually with 13 experts with the aims of gaining relevant and insightful information for IC, IWE and business performance cohesion. From a pilot study of 49 Bumiputera SME entrepreneurs, the findings indicate that intellectual capital components and Islamic work ethics are vital for performance management practices in the firm. Contribution/ Originality: Theoretically, this study generalizes intellectual capital and Islamic work ethics in SME setting and is a preliminary impetus for exploring Bumiputera intellectual capital, Islamic work ethics and business performance. Practically, it provides valuable references for entrepreneurs, giving a prioritized array of crucial resources that allows Bumiputera SMEs to sustain the competitive advantage.